ANALISIS KEMAMPUAN KONEKSI MATEMATIS DITINJAU DARI MINAT BELAJAR SISWA PADA MATERI TEOREMA PHYTAGORAS BERBANTUAN QUIZIZZ - Khadijah, Dhea Marlianti; Arwanto, Arwanto; Sumliyah, Sumliyah (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
This research aims to analyze mathematical connection abilities in terms of students' learning interest in the Pythagorean theorem material with the help of Quizzizz. This type of research is qualitative survey research using instruments with the help of mathematical connection tests, learning interest questionnaires and interview guides. The research subjects in this study were taken using a purposive sample. The data analysis technique used is data reduction, data presentation and finally drawing conclusions. The subjects of this research were students of SMPN 1 Sumber consisting of 31 students in class VIII.. The results of data analysis show that there is a comparable relationship between students' interest and mathematical connection abilities. The mathematical connection abilities of students at SMPN 1 Resources for class VIII in the Pythagorean theorem material assisted by Quizzizz are in the medium category. There are 9 students in the high category, 21 students in the medium category and 1 student in the low category. This shows that students are able to relate and relate mathematics to concepts, other sciences and in everyday life. Students' learning interest in class VIII Pythagorean theorem material at SMPN 1 Sumber is in the medium category. There are 4 students in the high category, 21 students in the medium category and 5 students in the low category. This shows that students' interest in learning about the Pythagorean theorem material is quite good